Theoretical physicist identity development: A critical account of factors influencing progression from novice to expert - Cornell, Alan; Padayachee, Kershree (Critical Studies in Teaching and Learning, 2023)
In a context of rapid change in higher education and work, lecturers are still expected to provide meaningful learning experiences that enculturate students to disciplinary knowledge, values, and practices. Within the STEM disciplines, this process of enculturation is premised on the existence of an underpinning ‘culture of science’ defined by long-established discipline-specific discourses that include values, models of thinking, patterns of behaviour and even language conventions. In this reflective autoethnographic study, we apply Carlone and Johnson’s ‘science identity’ framework to analyse the reflections of a theoretical physics lecturer on the journey to becoming a theoretical physicist. The analysis reveals the factors (implicit and explicit) that may enhance or constrain academic progression. These factors are discussed in relation to implications for students from diverse backgrounds, and the critical role played by lecturers in revealing the ‘rules of the game’.